Peran Keikutsertaan Mahasiswa FISIP Universitas Teknologi Sumbawa dalam Organisasi terhadap Pola Pikir Kritis - Apriliansyah, Elga; Iman, Topan Rahmatul (Lembaga Yasin AlSys, 2024)
This research discusses the influence of the participation of students from the Faculty of Social and Political Sciences, Sumbawa Technology University in organizations on critical thinking patterns. The problem formulation that will be discussed in this research is the role of participation in organizations in changing the critical thinking patterns of students at the Faculty of Social and Political Sciences. This research aims to determine the role of participation in organizations on changes in the critical thinking patterns of students at the Faculty of Social and Political Sciences. This research uses a descriptive qualitative research method, namely describing the data as it is and explaining the data or events with qualitative explanatory statements to obtain in-depth information, as well as data that contains significant meaning and can influence the research object. This research produced several results. Students get the opportunity to develop thinking patterns, analytical thinking skills, as well as communication and negotiation skills. The participation of students from the Faculty of Social and Political Sciences in student organizations that encourage debate and discussion activities provides important benefits. These discussions and debates train students in critical thinking, develop communication skills, and convey opinions clearly and persuasively.